Antibacterial Activity of Seaweed Extract and its Effects on the DNA Sequence of Selected Essential Genes of Staphylococcus Aureus - Mashan, Nurmas Idayu (2007)
Mortality rate caused by bacteria infections is increasing to nearly 20 million deaths each year, world wide. One of the common causes contributing to the death is the increasing number of antibiotic resistance pathogens including Methicillin Resistant Staphylococcus aureus (MRSA), Extended Spectrum Beta Lactamase (ESBL) organisms, and Multiple Drug Resistant Organism (MDRO). Therefore, this study was designed to explore an alternative antibacterial product derived from seaweed extracts, Gracilaria changii and Euchema denticulatum, through several approaches including bioassays and molecular biology tools especially the study of DNA and RNA encoding genes of interest in MRSA and non-MRSA. Bioassay studies revealed that G. changii and E. denticulatum extracts showed inhibitory activity only on gram positive organisms tested including S. aureus and Streptococcus pyogenes which were expressed in terms of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) test. Thus,gram negative pathogens tested including Escherichia coli, Vibrio cholerae, Klebsiella pneumoniae and Pseudomonas aeruginosa showed resistant phenotypic pattern to both extracts. Since G. changii and E. denticulatum extracts showed inhibitory activity against S. aureus, five genes in this pathogen were chosen to study the effect of both seaweed extracts on the genes through PCR and RT-PCR analysis. The results indicated genes for DNA repair, adaB; cell wall biogenesis gene, sav1017; and mecA gene yielding substantial effect by showing changes in the sequence of the genes. Based on the changes in the selected gene sequences of treated S. aureus isolates, the inhibitory activity for both seaweeds extracts on the respective genes is predicted according to the function of each gene. G. changii and E. denticulatum extracts were predicted to interfere with the function of adaB gene in producing the methyltransferase enzyme which was involved in the DNA repair in S. aureus. Both extracts were also predicted to interfere with the activity of sav1017 gene in producing UDP-N-Acetylglucosamine transferase enzyme which is involved in the peptidoglycan synthesis in S. aureus since peptidoglycan is the major component in the cell wall of bacteria. However, the predicted inhibitory mechanism of both seaweeds extracts on mecA gene cannot be speculated based on the present research approach. As a conclusion, G. changii and E. denticulatum extract can be categorized as a narrow spectrum antibacterial agent against S. aureus and S. pyogenes in vitro. The effectiveness of both seaweed extracts in affecting cell wall synthesis and DNA repair gene in S. aureus has significant conotation. The finding of antibacterial activity by both extracts against MRSA and non-MRSA strains is hoped to have potential in producing alternative antibacterial agents from natural resources, against resistant S. aureus to reduce the infections and fatality.